Pengembangan Buku Saku Kesehatan sebagai Media Edukasi pada Pasien COVID-19 yang Menjalani Isolasi Mandiri - Lolita Lolita; Azis Ikhsanudin; Yuniar Nabilla Ligawa; Nidaul Makwa; Febrilla Ayu Larasati; Rachmawati Sukmaningtyas; Nabila Nabila; Asiilah Fatihatul Khoirot; Putri Hanisari; Faril Gunanti; Merry Ramdhani (Jurnal Surya Masyarakat, 2023)
Coronavirus Illness (COVID)-19, an infectious respiratory illness were first dicscovered in Wuhan, China in 2019. This diseases has become a global pandemic which spread quiclkly worldwide.  In order to combat this pandemic, it is critical that health efforts must be carried out by all segments of society. Health education is one of the health initiatives, particularly for COVID-19 patients who are experiencing self-isolation.  The availability of COVID-19 health education pocket books may help them in better understanding  about COVID-19. The method of health education is to provide a pocket book named "Serba-Serbi COVID-19" in both softfile and hardfile format to patients undergoing self isolation in the Umbulharjo I, Umbulharjo II, and Kotagede II Health Centers,  Yogyakarta.  The materials presented  in the pocket book included iself isolation protocols for COVID-19 positive patients, the role of vaccination, strategies to identify hoax news and other materials related to therapy and prevention of COVID-19 infection. The pocket book assessment was conducted by media experts, material experts, and patients undergoing self-isolation at Umbulharjo I, Umbulharjo II, and Kotagede II health centers.  Two stages of pocket book evaluation by self isolation patients were completed. There were seven participants in the first round, and a total of thirty people took part in the second round. When the pocket book assessment was evaluated in stages one and two, the results revealed "very feasible" and "decent" for the six aspects of the assessment (benefits, size, material, visual display, language or vocabulary selection, presentation of pocket book). The feasibility study  of pocket book named "Serba-Serbi COVID-19" concluded that self islation COVID-19 patients who read and assessed the pocket book  could understood the material well.